Analisis faktor-faktor yang mempengaruhi harga saham dengan nilai perusahaan sebagai variabel intervening : (Studi Pada Perusahaan LQ45 di Bursa Efek Indonesia Periode 2020-2022) - Saidi, Saidi; Sujai, Yusuf Imam; Salim, Agus (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
This research to assess Solvability and Profitability and their effect on stock prices and business value, this study involves an analysis of several factors, including the Dept. to Equity Ratio, Return on Investment, Stock Price, and Price Book Value. Utilizing secondary data in the form of annual financial reports from 2020–2021, research was conducted on LQ45 companies. The analysis tool used is SmartPLS. The list of LQ45 business actors registered on the Indonesia Stock Exchange from 2020 to 2022 is the basis for selecting the research population. A total of 98 financial reports from 32 companies are included in the sample selected based on the research criteria. The analysis results indicated that Solvability affects the company's value, while profitability does not have an impact. Additionally, both profitability and solvability do not have a significant influence on stock prices. However, stock prices are significantly influenced by the company's value. Solvability and profitability ratios do not show any observable impact on stock prices when the company's value is used as a mediator.